2018
DOI: 10.1017/s0959270918000254
|View full text |Cite
|
Sign up to set email alerts
|

Opposing population trajectories in two Bustard species: A long-term study in a protected area in Central Spain

Abstract: SummaryIn conservation biology, population monitoring is a critical step, particularly for endangered groups, such as steppe birds in European agro-ecosystems. Long-term population monitoring allows for determination of species population trends and also provides insights into the relative roles that environmental variability and human activities have on priority species. Here, we compare the population trends of two sympatric, closely related farmland bird species, the Little Bustard Tetrax tetrax and Great B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The loss of agro-steppe habitat is one of the factors behind little bustard's population declines observed in recent decades. In Portugal little bustards declined by 49% between 2003-2006(Silva et al, 2018, with similar trends found in some protected areas in Spain (Casas et al, 2019).…”
Section: Impacts Of Agro-steppe Area Loss On Great Bustard Populationssupporting
confidence: 75%
“…The loss of agro-steppe habitat is one of the factors behind little bustard's population declines observed in recent decades. In Portugal little bustards declined by 49% between 2003-2006(Silva et al, 2018, with similar trends found in some protected areas in Spain (Casas et al, 2019).…”
Section: Impacts Of Agro-steppe Area Loss On Great Bustard Populationssupporting
confidence: 75%
“…The trend of the TRIM population index can be used as an estimate of annual variations in the abundance of bird species ( Gordo, 2018 ; Stjernman et al, 2013 ) (see ( Traba & Morales, 2019 ) for a similar procedure). Indeed, the SACRE program provides the best information of population trends for common breeding bird species in Spain ( SEO/BirdLife, 2016 ; Casas et al, 2019 ). The indices of a group of species can be summarized into a single estimate to analyze trends of related bird species ( Bowler et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Grape vines are grown either in a traditional way-free standing without any attachment (goblet-shaped)-or as trellised vines with partial irrigation. The area has been highlighted as a hot spot for steppe birds (Traba et al 2007) and supports a significant population of breeding Little Bustards, which has declined steeply in recent years (Casas et al 2019).…”
Section: Study Area and Speciesmentioning
confidence: 99%
“…Each year, 110 ± 8 (mean ± SD) of those points were surveyed (range 91-116). Little Bustards observed from each point were plotted on a map, and double counting among consecutive points was avoided (if a bird was spotted in the same place, it was considered to be the same individual as in the nearby point and was not counted again [see Casas et al 2019 for more details]). We detected both males and females, but most observations were of males; females accounted for about 13% of the total 1489 Little Bustard observations over the years.…”
Section: Little Bustard Abundance and Habitat Datamentioning
confidence: 99%
See 1 more Smart Citation